2022
DOI: 10.1111/caje.12592
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of multiple jobholding in Canada

Abstract: In Canada, the fraction of workers holding multiple jobs has almost tripled since the mid-1970s. In this paper, we document this historical change and provide a comprehensive account of its dynamics. We use restricted-access panel micro-data from the Canadian labour force survey to construct transition probabilities in and out of multiple jobholding. We analyze these data through the lens of a trend decomposition that separates out the role of worker inflows and outflows. The upward trend in multiple jobholdin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Average working hours for single job spells are 36.6 per week, while that for multiple job spells are 62.1 per week. It is consistent with the findings ofKostyshyna and Lalé (2022), as they found that two-thirds of the multiple job spells are used to increase working hours. Average employment duration for single job spells (106 weeks) is longer than multiple job spells (34 weeks), suggesting that multiple job holdings are short-term in nature.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Average working hours for single job spells are 36.6 per week, while that for multiple job spells are 62.1 per week. It is consistent with the findings ofKostyshyna and Lalé (2022), as they found that two-thirds of the multiple job spells are used to increase working hours. Average employment duration for single job spells (106 weeks) is longer than multiple job spells (34 weeks), suggesting that multiple job holdings are short-term in nature.…”
supporting
confidence: 90%
“…As an example, people hold the second job to obtain nonpencuniary benefits unprovided by the first job (e.g., enjoyment or insurance against unemployment risks). Kostyshyna and Lalé (2022) found that there was an increasing trend of multiple job holdings, two-thirds of which were caused by hours constraints and one-third were caused by nonpencuniary benefits. Models considering both reasons for multiple job holdings were discussed in Oaxaca and Renna (2006) and Hlouskova et al (2017).…”
Section: Introductionmentioning
confidence: 99%